2015
DOI: 10.5501/wjv.v4.i1.13
|View full text |Cite
|
Sign up to set email alerts
|

What psychiatric screening and monitoring might be needed with the new generation of hepatitis C treatments?

Abstract: have emerged. These significantly boost the likelihood of sustained viral response, including for genotype 1, and do not seem to have the side effects of interferonalpha or ribavirin. Relevant data are reviewed to assess the degree that these new treatments might reduce the portion not eligible for treatment due to psychiatric comorbidities, and might reduce the emergence of psychiatric symptoms during treatment. Several organizations have recently released evidence-based treatment recommendation guidelines. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Psychiatric morbidity in patients with HCV infection is elevated and otherwise eligible patients have frequently not received treatment because of the fear of an exacerbation of psychiatric symptoms [ 4 , 7 9 ]. A few studies suggest psychiatric comorbidity and drug abuse to be risk factors for non-adherence and not attaining sustained viral response (SVR) [ 10 12 ], whereas several other studies have demonstrated similar rates of adherence and SVR in patients with HCV infection and psychiatric comorbidity (including drug abuse) [ 13 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychiatric morbidity in patients with HCV infection is elevated and otherwise eligible patients have frequently not received treatment because of the fear of an exacerbation of psychiatric symptoms [ 4 , 7 9 ]. A few studies suggest psychiatric comorbidity and drug abuse to be risk factors for non-adherence and not attaining sustained viral response (SVR) [ 10 12 ], whereas several other studies have demonstrated similar rates of adherence and SVR in patients with HCV infection and psychiatric comorbidity (including drug abuse) [ 13 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The side effect profile of DAAs compared with previous HCV medications is reported to be less severe [ 26 ] and patient-reported outcomes (PROs) improved [ 27 , 28 ]. Although there are efficacy studies with DAAs that include patients with psychiatric comorbidity, [ 29 , 30 ], few studies have specifically addressed psychiatric symptoms in DAA treatment [ 7 , 13 ]. A recent retrospective study that excluded patients with substance abuse and prior IFN-based treatment found that symptoms of depression decreased after treatment with DAA.…”
Section: Introductionmentioning
confidence: 99%
“…US Food and Drug Administration (FDA) prescribing information for recent drugs, that are FDA approved, do not note psychiatric symptoms as recognised side effects 20. Clinical trial ‘data indicate that these no interferon-alpha/no ribavirin regimens are far more well tolerated by patients, do not seem to have notable psychiatric contraindications and the type of psychosocial assessment for these regimens are typical in medical care' 7…”
Section: Introductionmentioning
confidence: 99%